Handbook of psychophysiology - Cacioppo John T. (Cambridge University Press, 2017)
"The first Handbook of Psychophysiology was published more than four decades ago (Greenfield & Sternbach, 1972). Coverage in that Handbook emphasized the peripheral nervous system, an emphasis that many still identify with the term psychophysiology in accord with the history of psychophysiology"--
Keywords: Psychophysiologie; Médecine comportementale; Manuels d'enseignement supérieur